Why Teach? : Notes and Questions From a Life in Education - Nehring, James (Lanham, Maryland Rowman & Littlefield, 2015)
One year out of college, James Nehring landed accidentally in teaching and soon discovered his love for the profession. But he was surrounded by a school system consumed with order, efficiency, rules, and punishment. He wanted to change the system. So began a quest that became a career. This book is a journey inside American education and a story of self-discovery. Why Teach? is an introductory text for an aspiring teacher, a source of reflection for fellow educators, and an insider critique of the system from pre-school to graduate school. In an age dominated by social science, Why Teach? makes the case for a humanistic approach to schooling
Keywords: Teachers -- Teaching -- Education, Humanistic